A Study Of Sulphate Attack Resistant On Fired Clay Masonry Units - Cheng, Kai Lee (Universiti Sains Malaysia, 2005)
This dissertation reports the study of the sulphate attack resistance of fired clay bricks. Five types of fired clay bricks had been selected to investigate their ability on sulphate attack resistance. Besides that, study of material property and mechanical property of fired clay bricks had been conducted to determine its influence on the sulphate attack resistance of fired clay bricks. This study needs to define which type of fired clay bricks has sulphate attack resistance. Besides that, this study also stresses on the important of choosing the suitable sulphate attack fired clay bricks to construct buildings at area exposed to sulphate attack. This information is important in helping designer to improve the durability of fired clay bricks when producing sulphate attack resistance fired clay bricks. However, raw materials of fired clay bricks are not defined in this study due to the lack of information about it. A series of laboratory test had been carried out to investigate the material properties and mechanical properties of five types of fired clay bricks. Sulphate attack resistance of fired clay bricks had been observed from cycle test by measuring the number of cycles which causes the brick samples to fail. Relationship between properties of fired clay bricks and its resistance to the sulphate attack was defined. This study will provide more information in choosing the suitable sulphate attack resistance fired clay bricks